The Visum Et Repertum Forensic Examination as Evidence of a Rape Crime in the Trial Process of Kupang District Court - Siti Syahida Nurani1, Absori Absori2, Khudzaifah Dimyati3, Kelik Wardiono4, Zainur Wula5, Arief Budi (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research aims to prove visum et repertum as an evidence of a rape crime in the trial process at Kupang District Court (PN Kupang), so as to know how the judge assembly accommodate all evidences in the court as a basis to make a verdict, regading the weight of the punishment which will be given the rape crime perpetrator. This is a juridical- empirical descriptive research, as it uses primary and secondary data in the form of the judges’ verdict at the rape crime trial which is absolute and also interviews conducted to subjects who are involved in the research. The health aspect in proving the rape case is evidenced in the visum et repertum papers and expert information from the doctors who examined the victim.